EDUCAÇÃO EM SAÚDE COM AS CRIANÇAS DO POVO PATAXÓ HÃ-HÃ-HÃE: APRENDIZADOS E DIVERSÃO - Oliveira, Roberta Ellen Santos; Silva, Dayane Jhenifer Ribeiro; Ferreira, Grasiele Cristine; Pereira, Samira Auxiliadora (Sinapse Múltipla, 2020)